2022
DOI: 10.18632/aging.204427
|View full text |Cite
|
Sign up to set email alerts
|

Qi Ling decoction enhances abiraterone treatment via suppression of autophagy in castration resistant prostate cancer

Abstract: Abiraterone acetate has exhibited impressive results in improving progression-free survival of patients with metastatic castration-resistant prostate cancer. However, many patients may develop abiraterone resistance with a variable duration of response. Hence, identifying a remedy to overcome abiraterone resistance is critical for patients with castration-resistant prostate cancer. In this study, we aim to explore the potential of Qi Ling decoction (QLD), a traditional Chinese medicine, in attenuating abirater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“… 22 To explore the regulatory mechanism of autophagy in prostate cancer and develop related drugs for autophagy may provide a new method for the treatment of prostate cancer. 23 We also revealed that CHD affected the progression of prostate cancer by suppressing autophagy. In addition, oxidative stress is related to the occurrence of prostate hyperplasia and prostate cancer.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“… 22 To explore the regulatory mechanism of autophagy in prostate cancer and develop related drugs for autophagy may provide a new method for the treatment of prostate cancer. 23 We also revealed that CHD affected the progression of prostate cancer by suppressing autophagy. In addition, oxidative stress is related to the occurrence of prostate hyperplasia and prostate cancer.…”
Section: Discussionmentioning
confidence: 79%
“…In the process of tumor pathogenesis, autophagy plays a “double‐sided role,” which can not only fight cancer but also promote cancer development 22 . To explore the regulatory mechanism of autophagy in prostate cancer and develop related drugs for autophagy may provide a new method for the treatment of prostate cancer 23 . We also revealed that CHD affected the progression of prostate cancer by suppressing autophagy.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, Feng et al [51] studied Qi Ling decoction (QLD), a Chinese herb, in combination with abiraterone using PC-3 and DU145 cells that were developed to be abiraterone resistant. Using flow cytometry and CCK-8 assays, QLD in combination with abiraterone resulted in decreased cell survival together with robust apoptosis in the resistant cell lines as compared to each drug alone.…”
Section: Abiraterone and Autophagymentioning
confidence: 99%